THE EFFECT OF DISTRIBUTION INTEGRATION AND SUPPORT SERVICE OF EXPORT DOCUMENT ON OVERALL PERCEPTION OF SERVICE EXCELLENCE AT PT MITRA KARGO INDONESIA - Natalia Dessy Permatasari; Lusia Maria Silitonga; Andi - Setiawan (Admisi dan Bisnis, 2016)
The competition among freight forwarding isstrict. This research analyzes the effect ofDistribution Integration and Support Serviceof Export Document on Overall Perception ofService Excellence at PT Mitra KargoIndonesia, Semarang as freight forwardingcompany. This research used a multiple linearregression. The primary data used in thisresearch is collected from questionnaire. Theamounts of the respondents are 45 who areexporters of PT Mitra Kargo Indonesia. Theresult shows that analysis which is carried outby SPSS 16, from coefficient of adjusted Rsquared(R2) reveals that the independentvariable (Integration of Distribution – X1 andSupport Service of Export Document – X2)affected on dependent variable (Perception ofService Excellence – Y) amount of 63,5%.Whereas other factors are amount of 36,5%which is out of this research.